Prioritas Kemaslahatan Anak (Maslahah) Dalam Penyelesaian Sengketa Hadhanah Berdasarkan Tinjauan Kaidah Fiqiyah - M. Ridho Firdaus; Hendri Sayuti (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The determination of child custody (hadhanah) after divorce is one of the crucial issues in Islamic family law. Often, these disputes center on the ego-sectoral rights of parents, even though Islamic law places the welfare of children (maslahah al-atfal) as the highest priority. This study aims to analyze how Fiqh principles, as one of the methodologies of Islamic law, serve as the legal and philosophical basis for Religious Court judges in prioritizing the best interests of the child. Using qualitative research methods through a legal-normative approach and literature study, this research examines the application of the principle of “Ad-dhararu yuzāl” (Harm must be eliminated). The results of the study show that Fiqh Rules provide flexibility for judges to go beyond the textual provisions of classical fiqh, which are sometimes gender biased, towards decisions that are substantial and oriented towards the psychological, physical, and spiritual protection of children amid the dynamics of modern society.